KORELASI DISIPLIN DALAM PEMBELAJARAN PAI DENGAN RELIGIUSITAS (Studi Kasus Siswa Kelas IX SMP Negeri 1 Adipala Tahun Ajaran 2019/2020) - Kristiyowati, Endah; Anis Afiqi, Muhammad (Jurnal Tawadhu, 2021)
This study aims to find out how Discipline in PAI Learning Class IX Adipala 1 Junior High School Students, to find out how Religiosity of Class IX Adipala 1 Junior High School Students and to know the Relationship Between Discipline in PAI Learning with Religiosity of Class IX Students of Adipala 1 Public Middle School in 2019 Academic Year / 2020. This research is a quantitative research with a population of 40 respondents. To explore data, this study uses a questionnaire method that is distributed to respondents to be filled. In addition to obtaining data that can support research, researchers use observation methods, as well as documentation. The results showed that Discipline in PAI Learning was good, and the Religious Students of Adipala 1 Public Middle School were good. Based on data analysis conducted using the Product Moment Correlation Technique from Corrected Item-Total Correlation, the correlation number between the Discipline variables in PAI Learning and Student Religiosity is rxy = 0.450, it means rxy> r table, at 5% significance level (0.450 > 0.312). This means that between the two variables there is a positive correlation or correlation that goes in the same direction and significant, meaning that the higher the Discipline in PAI Learning with the higher Student Religiosity and vice versa the lower Discipline in PAI Learning correlates with the lower Student Religiosity.